Inspired by Calvin Lin - Part III

Algebra Level 5

( x + 17 ) 2 + ( 2 x + 16 ) 2 + ( 3 x + 15 ) 2 + + ( 16 x + 2 ) 2 + ( 17 x + 1 ) 2 = 0 (x+17)^2+(2x+16)^2+(3x+15)^2+\ldots+(16x+2)^2+(17x+1)^2=0

If α \alpha and β \beta are the roots of the equation above, and suppose α + β α β = a b | \alpha + \beta - \alpha \beta | = \frac a b for coprime positive integers a , b a,b , find the value of a + b a+b .


The answer is 108.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

( x + 17 ) 2 + ( 2 x + 16 ) 2 + ( 3 x + 15 ) 2 + . . . + ( 16 x + 2 ) 2 + ( 17 x + 1 ) 2 = 0 k = 1 17 [ k x + ( 18 k ) ] 2 = 0 k = 1 17 [ k 2 x 2 + 2 k ( 18 k ) x + ( 18 k ) 2 ] 2 = 0 x 2 k = 1 17 k 2 + 2 x ( 18 k = 1 17 k k = 1 17 k 2 ) + k = 1 17 k 2 = 0 17 ( 18 ) ( 35 ) 6 x 2 + 2 x ( 18 × 17 ( 18 ) 2 17 ( 18 ) ( 35 ) 6 ) + 17 ( 18 ) ( 35 ) 6 = 0 35 x 2 + 2 x ( 3 × 18 35 ) + 35 = 0 35 x 2 + 38 x + 35 = 0 \begin{aligned} (x+17)^2+(2x+16)^2+(3x+15)^2+...+(16x+2)^2+(17x+1)^2 & = 0 \\ \sum_{k=1}^{17} {[kx +(18-k)]^2} & = 0 \\ \sum_{k=1}^{17} {[k^2x^2 +2k(18-k)x + (18-k)^2]^2} & = 0 \\ x^2 \sum_{k=1}^{17} {k^2} + 2x \left( 18 \sum_{k=1}^{17} {k} - \sum_{k=1}^{17} {k^2} \right) + \sum_{k=1}^{17} {k^2} & = 0 \\ \frac{17(18)(35)}{6}x^2 + 2x\left( 18\times \frac{17(18)}{2} - \frac{17(18)(35)}{6} \right) +\frac{17(18)(35)}{6} & = 0 \\ 35x^2 + 2x(3\times18-35) + 35 & = 0 \\ 35x^2 + 38x + 35 & = 0 \end{aligned}

Using Vieta formulas,

α + β = 38 35 \alpha + \beta = - \dfrac{38}{35} and α β = 1 \alpha \beta = 1

α + β α β = 38 35 1 = 73 35 = 73 35 \Rightarrow |\alpha + \beta - \alpha \beta | = \left|- \dfrac{38}{35}-1 \right| = \left| -\dfrac{73}{35} \right| = \dfrac{73}{35}

a + b = 73 + 35 = 108 \Rightarrow a + b = 73+35 = \boxed{108}

Moderator note:

There's an easy way to show that α β = 1 \alpha \beta = 1 , so, the majority of your working could be focused solely on finding the value of α + β \alpha + \beta .

Bonus question : Find a general formula to determine A n + B n A_n + B_n if A n A_n and B n B_n are the roots to the equation k = 1 n [ k x + ( n k + 1 ) ] 2 = 0 \displaystyle \sum_{k=1}^n [kx + (n-k+1)]^2 = 0 .

Done. Sorry, I used a spreadsheet to do the calculations. Factorization wasn't important.

Chew-Seong Cheong - 6 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...